Refining the tightness and looseness framework with a consumer lens. Issue 3 (12th April 2017) - Lin, Lily; Dahl, Darren W.; Argo, Jennifer J.
Abstract: In their paper, Li, Gordon and Gelfand (this issue) introduced the Tightness–Looseness (T–L) framework to the consumer domain, and offered several ideas on how this framework could be applied to consumer behavior. In this commentary, we examine the T–L framework through the consumer lens and discuss how the uniqueness of the consumption context can refine and broaden this psychological framework. We identify four questions that aim to enrich our discussion of this framework from the perspective of consumer research, and to motivate future research questions. Specifically, we consider 1) how the interplay between the tightness/looseness of a culture and its effect on consumer behavior can be a bi‐directional relationship, 2) how variances in T–L in different consumption subcultures and aspects of society (e.g., economic, political) can impact consumer behavior, 3) how the examination of T–L at different stages in the consumption process is a relevant and important question to consider, and 4) how T–L may contribute to further investigation and understanding of punishment toward business and consumer norm violators.